Anti-SARS-CoV-2 serology based on ancestral RBD antigens does not correlate with the presence of neutralizing antibodies against Omicron variants - Léa Dépéry; Isabelle Bally; Axelle Amen; Benjamin Némoz; Marlyse Buisson; Laurence Grossi; Aurélie Truffot; Raphaële Germi; Delphine Guilligay; Mélanie Veloso; Antoine Vilotitch; Olivier Epaulard; et al. (Microbiology Spectrum)
ABSTRACT Neutralizing antibody titers and binding antibody levels are considered correlates of protection against severe SARS-CoV-2 infection. The clinical utility of serology should be reevaluated in light of the emergence of escape variants, as commercial antibody-binding assays have not been adapted to the virus’ antigenic evolution. We compared anti-SARS-CoV-2 antibody titers in four quantitative serological tests based on variable ancestral spike antigens (three in-house ELISAs and the prototype VIDAS SARS-CoV-2 IgG QUANT assay) and neutralization assays against the pseudotyped Wuhan, BA.2, BA.4/5, BQ.1.1, and XBB.1.1 viruses in a cohort of 100 patients infected in 2020 or during the Omicron waves. Binding antibody levels correlated well with neutralizing antibody titers for Wuhan, BA.2, and BA.4/5, but the association decreased for BQ.1.1 and XBB.1 (for the VIDAS assay, Spearman’s correlation was 0.82 [95% CI 0.74–0.88] and 0.61 [0.46–0.72] for BA.2 and XBB.1, respectively). In 15% of patients with no neutralizing antibodies against XBB.1, the VIDAS assay still yielded binding antibody levels ranging from 74 to 7,652 binding antibody units/mL. Using an adjusted threshold based on receiver operating characteristic (ROC) curve analysis, the specificity of neutralizing antibody detection increased from 0.15 (95% CI 0.02–0.45) and 0.17 (0.04–0.41) to 0.92 (0.64–1.00) and 0.83 (0.59–0.96) against BQ.1.1 and XBB.1, respectively. Serological tests based on receptor-binding domain antigens from the ancestral virus fail to predict neutralizing activity against the latest circulating Omicron variants. Adapting serological tests may improve their clinical utility in immunocompromised patients.IMPORTANCEAnti-SARS-CoV-2 serology was developed in 2020 in response to the COVID-19 pandemic to diagnose SARS-CoV-2 infection and monitor an individual’s immunity following natural infection or vaccination. Given the relationship between neutralizing antibody titers and protection against severe infection, many studies have evaluated the correlation between serology tests and neutralization assays in the pre-Omicron era. An important potential clinical use of serology, which explores binding antibodies, is estimating an individual’s level of protection against new infection, particularly in immunosuppressed individuals and those at risk of severe COVID. However, in the Omicron era, as new viruses evade the immunity induced by previous infections and vaccination, the correlation between binding antibody levels determined by serological assays developed from ancestral antigens and neutralizing antibody titers against new viruses should be re-examined in order to determine whether these assays should be optimized by adapting antigens to the circulating SARS-CoV-2 strains.